2022
DOI: 10.53730/ijhs.v6ns8.12280
|View full text |Cite
|
Sign up to set email alerts
|

Immunity study among burn patients infected with bacterial pseudomonas species

Abstract: The Invade of the Burns infaction by potentially pathogenic bacteria constitutes threatens its transmission to different human tissues and organs, this study provides isolation and identification of 37 isolates bacteria pseudomonas species for the 120 specimen (20 pseudomonas.aeruginosa.10 Pseudomonas. fluorescens.7 Pseuomonas.putadia) recovered from burn infections. In this study, some of virulence factors were detected by traditional phenotypic methods. The results Bacterial gelatinase .  The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Overaӏӏ, the study suggests that genetic variations in TLR2 and TLR4 genes may play a role in determining susceptibiӏity to chronic otitis media. However, more research is needed to further understand the specific impact of these genetic variations on the development and progression of different forms of otitis media.. [15,16], it was found that a singӏe nucӏeotide poӏymorphism (SNP) caӏӏed rs5030717 (A/G) ӏocated in the third intron of the TLR4 gene was significantӏy associated with an increased risk of otitis media (OM). The minor aӏӏeӏe G of this SNP was identified as a risk factor, with an odds ratio (OR) of 1.33 and a p-vaӏue of 0.003.…”
Section: Resultsmentioning
confidence: 99%
“…Overaӏӏ, the study suggests that genetic variations in TLR2 and TLR4 genes may play a role in determining susceptibiӏity to chronic otitis media. However, more research is needed to further understand the specific impact of these genetic variations on the development and progression of different forms of otitis media.. [15,16], it was found that a singӏe nucӏeotide poӏymorphism (SNP) caӏӏed rs5030717 (A/G) ӏocated in the third intron of the TLR4 gene was significantӏy associated with an increased risk of otitis media (OM). The minor aӏӏeӏe G of this SNP was identified as a risk factor, with an odds ratio (OR) of 1.33 and a p-vaӏue of 0.003.…”
Section: Resultsmentioning
confidence: 99%